Genome-wide Mapping of the Coactivator Ada2p Yields Insight into the Functional Roles of SAGA/ADA Complex in Candida albicans - Sellam, Adnane (The American Society for Cell Biology, 2009)
The SAGA/ADA coactivator complex, which regulates numerous cellular processes by coordinating histone acetylation, is widely conserved throughout eukaryotes, and analysis of the Candida albicans genome identifies the components of this complex in the fungal pathogen. We investigated the multiple functions of SAGA/ADA in C. albicans by determining the genome-wide occupancy of Ada2p using chromatin immunoprecipitation (ChIP). Ada2p is recruited to 200 promoters upstream of genes involved in different stress-response functions and metabolic processes. Phenotypic and transcriptomic analysis of ada2 mutant showed that Ada2p is required for the responses to oxidative stress, as well as to treatments with tunicamycin and fluconazole. Ada2p recruitment to the promoters of oxidative resistance genes is mediated by the transcription factor Cap1p, and coactivator function were also established for Gal4p, which recruits Ada2p to the promoters of glycolysis and pyruvate metabolism genes. Cooccupancy of Ada2p and the drug resistance regulator Mrr1p on the promoters of core resistance genes characterizing drug resistance in clinical strains was also demonstrated. Ada2p recruitment to the promoters of these genes were shown to be completely dependent on Mrr1p. Furthermore, ADA2 deletion causes a decrease in H3K9 acetylation levels of target genes, thus illustrating its importance for histone acetyl transferase activity.